Trace element bioaccumulation, tissue distribution, and elimination in odontocetes stranded in Florida and Georgia, USA over a 15-year period (2007–2021) - Annie Page; Clara Hay; Wendy Marks; Baylin Bennett; Matthew O. Gribble; Wendy Noke Durden; Megan Stolen; Teresa Jablonski; Nadia Gordon; Trip Kolkmeyer; Mingshun Jiang; Nicole Pegg; et al. (Heliyon, 2024)
Odontocetes obtain nutrients including essential elements through their diet and are exposed to heavy metal contaminants via ingestion of contaminated prey. We evaluated the prevalence, concentration, and tissue distribution of essential and non-essential trace elements, including heavy metal toxicants, in tissue (blubber, kidney, liver, skeletal muscle, skin) and fecal samples collected from 90 odontocetes, representing nine species, that stranded in Georgia and Florida, USA during 2007–2021. Samples were analyzed for concentrations of seven essential (cobalt, copper, iron, manganese, molybdenum, selenium, zinc) and five non-essential (arsenic, cadmium, lead, mercury, thallium) elemental analytes using inductively-coupled plasma mass spectrometry. Risso's dolphins (Grampus griseus) and short-finned pilot whales (Globicephala macrorhynchus) had the highest median concentrations of mercury, cadmium, and lead, while dwarf sperm whales (Kogia sima) had the lowest. Adult pygmy and dwarf sperm whales that stranded in 2019–2021 had higher concentrations of arsenic, copper, iron, lead, manganese, selenium, thallium, and zinc compared to those that stranded in 2010–2018, suggesting an increasing risk of exposure over time. The highest concentrations of many elements (e.g., cadmium, cobalt, copper, manganese, molybdenum, thallium, zinc) were in fecal samples, illustrating the usefulness of this noninvasively collected sample. Aside from fecal samples, hepatic tissues had the highest concentrations of iron, manganese, mercury, molybdenum, and selenium in most species; renal tissues had the highest concentrations of cadmium; skin had the highest concentrations of zinc; and copper, arsenic, and lead concentrations were primarily distributed among the liver and kidneys. Phylogenetic differences in patterns of trace element concentrations likely reflect species-specific differences in diet, trophic level, and feeding strategies, while heterogeneous distributions of elemental analytes among different organ types reflect differences in elemental biotransformation, elimination, and storage. This study illustrates the importance of monitoring toxic contaminants in stranded odontocetes, which serve as important sentinels of environmental contamination, and whose health may be linked to human health.